Synopsis of the cockroach family Corydiidae (Blattodea: Corydioidea) in North America, with an identification key to subfamilies and genera, and taxonomic changes - Estrada-Álvarez, Julio César; de Luna, Manuel; García-Barrios, Roberto; Sormani-Hernández, Carlo Gilbert (Instituto de Ecología, A.C., 2022)
A synopsis of the cockroach family Corydiidae in North America (Canada, Mexico and the USA) is made. The diversity of this family in the region comprises 65 species grouped in eight genera and three subfamilies. Through the revision of type material, Myrmecoblatta hebardi Estrada-Álvarez & Guadarrama, 2013 is transferred to the genus Paralatindia Saussure, 1868; Latindia mexicana Saussure, 1868 is retransferred to the genus Compsodes Hebard, 1917; and Homoeogamia brasiliana (Saussure, 1864) is revealed to be a junior synonym of the Old World species Polyphaga aegyptiaca (Linnaeus, 1758). A checklist of the species for the region is presented, and a key to the subfamilies and genera is proposed.